Congenital amegakaryocytic thrombocytopenia with severe neurological findings. Issue 8 (December 2016) - Bör, Özcan; Turhan, Ayse B.; Yarar, Coskun
Abstract : Congenital amegakaryocytic thrombocytopenia (CAMT) is a rare autosomal recessive disorder characterized by thrombocytopenia from failure of megakaryopoiesis. The genetic background of CAMT is mutations in the myeloproliferative ligand gene encoding the thrombopoietin receptor. In our patient with CAMT, we identified homozygous missense mutations [c.407C>T (p.P136L)]. The association of CAMT and central nervous system (CNS) abnormalities is uncommon. Here we present a case in which CAMT appears linked to CNS abnormalities (encephalomalacia, global atrophy) and developmental delay related with intrauterine intracranial hemorrhage.